STRATEGI PENGEMBANGAN KOMPETENSI GURU DALAM MENINGKATKAN HASIL BELAJAR SISWA - Hufadz Nadiyya Kavina; Joko Sutarto; Barokah Isdaryanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this research is to identify strategies for developing teacher competencies to improve learning outcomes and the supporting factors of development effectiveness that influence teacher competencies. Using a qualitative research method based on a literature review of articles relevant to the research topic thru the academic databases Google Scholar and Publish or Perish. The research results show a positive relationship with teacher competency development strategies such as academic supervision and periodic mentoring programs. Supporting factors for the effectiveness of teacher competency development strategies include transformational leadership, intrinsic motivation of teachers, regulatory support, and the relevance of the program to field needs.